Capital structure and corporate governance : the role of hybrid financial instruments - Sasso, Lorenzo (Alphen aan den Rijn, The Netherlands : Kluwer Law International, 2013)
This thesis consists of a study of English and US corporate finance law and, in particular, the law in relation to hybrid financial instruments. Hybrids of financial instrument presents a mix of equity and debt characteristics. Therefore this thesis excludes from examination all the derivative instruments, while it focuses on two main types of hybrid security, in relation to their relevance to the situation studied: preference shares and convertible bonds. Despite a clear distinction in law between equity and debt, the development of sophisticated hybrid financial instruments has forced regulators to look beyond the legal form of an instrument to its practical substance. As observable in practice, the increase in financial innovation reflects the necessity of the parties to allocate control and cash-flow rights in a way that diverges from the classic allocation resulting from equity and debt. Most of the empirical and theoretical research in this area has focused on the tax advantages of issuing hybrids as a way of reducing the cost of capital or on their capacity to be subordinated to all the creditors and to be unable to trigger the liquidation of the firm in case of default on its payouts. However, very little contribution has been made to the analysis of these securities with regard to their implications for corporate governance. This thesis aims to discuss the rationale for issuing hybrids, and to evaluate the law relative to these instruments against the background of both agency costs and property rights theories. The functional approach unveils an important rationale for issuing hybrids. The UK and US have legal systems characterized by transactional flexibility. They rely heavily on ex post standards strategies to protect preference shareholders and on the judiciary to evaluate the fairness of a transaction. This flexibility places the UK and US legal systems among the most business-friendly countries. The vacuum left by mandatory company law in favour of a major flexibility in the market has pushed the parties to fill it contracting for their rights. In so doing they have facilitated the business relations and better protected themselves with careful drafting.
Introduction -- A historical perspective -- Distinguishing between equity and debt -- Settling the theoretical framework -- From the classification to the functional approach -- Significant corporate decisions -- Financing through hybrid instruments : risks opportunism and legal strategies for mitigation -- Control transactions -- Conclusive considerations.
Originally issued as author's thesis (doctoral) --London School of Economics and Political Science (University of London), 2012.
Includes bibliographical references (pages 193-215) and index.
Keywords: Hybrid securities -- Law and legislation; Corporate governance -- Law and legislation -- United Kingdom; Corporate governance -- Law and legislation -- United States; Corporation law -- United Kingdom; Corporation law -- United States